Catching profound optical flares in blazars. Issue 2 (28th January 2023) - Bhatta, Gopal; Zola, Staszek; Drozdz, M; Reichart, Daniel; Haislip, Joshua; Kouprianov, Vladimir; Matsumoto, Katsura; Sonbas, Eda; Caton, D; Pajdosz-Śmierciak, Urszula; Simon, A; Provencal, J; et al.
ABSTRACT: Flaring episodes in blazars represent one of the most violent processes observed in extra-galactic objects. Studies of such events shed light on the energetics of the physical processes occurring in the innermost regions of blazars, which cannot otherwise be resolved by any current instruments. In this work, we present some of the largest and most rapid flares captured in the optical band in the blazars 3C 279, OJ 49, S4 0954+658, TXS 1156+295, and PG 1553+113. The source flux was observed to increase by nearly ten times within a time-scale of a few weeks. We applied several methods of time series analysis and symmetry analysis. Moreover, we also performed searches for periodicity in the light curves of 3C 279, OJ 49 and PG 1553+113 using the Lomb–Scargle method and found plausible indications of quasi-periodic oscillations (QPOs). In particular, the 33- and 22-day periods found in 3C 279, i.e. a 3:2 ratio, are intriguing. These violent events might originate from magnetohydrodynamical instabilities near the base of the jets, triggered by processes modulated by the magnetic field of the accretion disc. We present a qualitative treatment as the possible explanation for the observed large amplitude flux changes in both the source-intrinsic and source-extrinsic scenarios.